Pendampingan Pastoral Bagi Umat yang Kawin - Cerai - Kawin Lagi - Sujianto, Paulus (Perspektif, 2020)
Based on the findings of a qualitative research this article examines the pastoral care for the remarried couples in the light ofthe Apostolic Exhortation ofAmoris Laetitia. The research took placein the “Dekenat Malang Kota” (ecclecial district of the city of Malang). It tries to explore the awareness of the remarried couples on their status and the various problems they may have to cope with. It focuses on the pastoral assistance the Church has offered for them. To some extent, the research is also intended to evaluate the practice of pastoral care for the remarried couples in the region. The writer argues that the assistance given to them basically wants to reveal God’s mercy. Therefore, the Church is expected to seriously take into consideration all aspects of pastoral care for the remarried couples as a manifestation of God’s love.